Viability of Phytoplankton from Ballast Waters of International Vessels Berthing at Ports of Cebu and Subic Bay, Philippines - Austero, Nero M.; Sawant, Subhash S.; Azanza, Rhodora V. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 31 No 1 (2019), 2019)
The viability of ballast water phytoplankton was assessed through incubation experiment. Leptocylindrus sp. and Thalassionema spp. were found to be viable when incubated in port water and ballast water media showing some increase in cell numbers. Bloom-forming diatom taxa, such as Chaetoceros spp. and Coscinodiscus spp. , potentially harmful diatom species Pseudo-nitzschia spp. , and dinoflagellates, Gambierdiscus spp. and Prorocentrum spp. were also identified in ballast waters from international vessels. These results further suggest possible successful transport of these organisms via shipping, which could facilitate the introduction and lead to bioinvasion in the local aquatic environment. Keywords: Ballast water, diatoms, dinoflagellates, phytoplankton, ports